Annual Plan 1966-67 Government of Himachal Pradesh - Planning Commission (Planning Commission, 1966)
As regards other Departments viz. Transport, Panchayats, etc. their outlay does not give specific indication of the funds meant for Kinnaur. But this area has not been neglected by them as their schemes will also serve this district within their overall programme.
Government of Himachal Pradesh, Planning and Development Department